Construção do modelo de comunicação de dados por ARINC 429 das aeronaves C295M da Força Aérea Portuguesa - Lazera, David (2022)
Júri: Presidente: MGen/EngEl/036605-G/Joaquim Gonçalves Coelho Lopes; Orientador: TCor/EngEl/083356-J/Delfim Zambujo das Dores; Co-Orientador: Cap/EngEl/128698-G/Ricardo José Ferreira Peralta; Vogal: Maj/EngEl/111524-D/Maria de Fátima Alves Nunes Bento